Activation of Akt and eIF4E survival pathways by rapamycin-mediated mammalian target of rapamycin inhibition - Sun, Shi-Yong; Rosenberg, Laura M; Wang, Xuerong; Zhou, Zhongmei; Yue, Ping; Fu, Haian; Khuri, Fadlo R (Cancer research (Chicago, Ill.), 2005)
The mammalian target of rapamycin (mTOR) has emerged as an important cancer therapeutic target. Rapamycin and its derivatives that specifically inhibit mTOR are now being actively evaluated in clinical trials. Recently, the inhibition of mTOR has been shown to reverse Akt-dependent prostate intraepithelial neoplasia. However, many cancer cells are resistant to rapamycin and its derivatives. The mechanism of this resistance remains a subject of major therapeutic significance. Here we report that the inhibition of mTOR by rapamycin triggers the activation of two survival signaling pathways that may contribute to drug resistance. Treatment of human lung cancer cells with rapamycin suppressed the phosphorylation of p70S6 kinase and 4E-BP1, indicating an inhibition of mTOR signaling. Paradoxically, rapamycin also concurrently increased the phosphorylation of both Akt and eIF4E. The rapamycin-induced phosphorylation of Akt and eIF4E was suppressed by the phosphatidylinositol-3 kinase (PI3K) inhibitor LY294002, suggesting the requirement of PI3K in this process. The activated Akt and eIF4E seem to attenuate rapamycin's growth-inhibitory effects, serving as a negative feedback mechanism. In support of this model, rapamycin combined with LY294002 exhibited enhanced inhibitory effects on the growth and colony formation of cancer cells. Thus, our study provides a mechanistic basis for enhancing mTOR-targeted cancer therapy by combining an mTOR inhibitor with a PI3K or Akt inhibitor.